Effects of active breaks on educational achievement in children with and without ADHD: study protocol and rationale of the Break4Brain project - Arenas, Diego; Bodi-Torralba, Miranda; Oliver, Andrea; Cantallops, Jaume; Ponseti, Francisco J.; Palou-Sampol, Pere; Collado, Juan A.; Flórez, Isabel; Galvez-Pol, Alejandro; Terrasa, Juan L.; Sitges, Carolina; Sánchez-Azanza, Víctor; et al. (Frontiers in Psychology, 2024)
The Break4Brain project aims to elucidate the effects of both acute and chronic physical activity (PA) on educational achievement in children with and without Attention Deficit Hyperactivity Disorder (ADHD). This study will be conducted in two phases: a cross-over design followed by a hybrid type 1 implementation-effectiveness trial, which includes both a cluster randomized controlled trial (RCT) and a qualitative study. In phase I, 60 children aged 10–12, with 30 each from ADHD and non-ADHD groups, will participate in a laboratory-based study over 4 days within 1 month. They will participate in three counterbalanced experimental conditions: (i) PA with cognitive engagement, (ii) PA without cognitive engagement, and (iii) a cognitively engaging control. This phase will assess acute changes in brain function, academic performance, working memory, inhibitory control, and sustained attention. Phase II will involve 600 children aged 10–12, randomly assigned to either a video-based PA program or a control group (300 children per group) in an 8-week cluster RCT. This phase will also incorporate a qualitative approach to explore the implementation context through pre- and post-intervention semi-structured interviews with teachers and school staff, and questionnaires for students. The outcomes of interest in this phase will include working memory, cognitive flexibility, selective attention, and academic performance. For the cross-over study, we hypothesize that PA conditions will enhance the studied outcomes compared to the control condition. In the RCT, we anticipate that the 8-week active breaks program will result in significant improvements in the selected outcomes compared to the control group. This study is expected to make pioneering contributions by including novel variables and focusing on the ADHD population. Furthermore, if the cluster RCT proves effective, it could offer a practical and cost-effective resource for integrating active breaks into daily school routines.